2015
DOI: 10.1136/postgradmedj-2015-133550
|View full text |Cite
|
Sign up to set email alerts
|

Ventricular arrhythmia storm in the era of implantable cardioverter-defibrillator

Abstract: In the era of widespread use of implantable cardioverter-defibrillators (ICDs) for both primary and secondary prevention of sudden cardiac death, a significant proportion of patients experience episodes of multiple ventricular tachycardia/fibrillation over a short period of time requiring device interventions. The episodes are termed ventricular arrhythmia (VA) or electrical storms. VA storm is a tragic experience for patients, with many psychological consequences. Current management for VA storms remains comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 74 publications
0
16
0
Order By: Relevance
“…2 The mechanism is likely mediated by a complex interplay between neurohormonal changes, abnormalities in calcium-related signaling and protein phosphorylation abnormalities, 29 and a predisposing electrophysiological substrate. 1 We showed that storm patients have different extent and distribution of endocardial low voltage scar on intracardiac mapping, specific to cardiomyopathy type that may help explain their electrophysiologic vulnerability. Although abnormalities in electrophysiology properties have been speculated, no study prior to ours has compared the electroanatomic mapping features of storm versus nonstorm patients.…”
Section: Discussionmentioning
confidence: 83%
See 4 more Smart Citations
“…2 The mechanism is likely mediated by a complex interplay between neurohormonal changes, abnormalities in calcium-related signaling and protein phosphorylation abnormalities, 29 and a predisposing electrophysiological substrate. 1 We showed that storm patients have different extent and distribution of endocardial low voltage scar on intracardiac mapping, specific to cardiomyopathy type that may help explain their electrophysiologic vulnerability. Although abnormalities in electrophysiology properties have been speculated, no study prior to ours has compared the electroanatomic mapping features of storm versus nonstorm patients.…”
Section: Discussionmentioning
confidence: 83%
“…Storm is recognized as a distinctive clinical arrhythmia syndrome with specific management and prognostic implications portending an increased risk of death, heart transplantation, and heart failure hospitalization . The mechanism is likely mediated by a complex interplay between neurohormonal changes, abnormalities in calcium‐related signaling and protein phosphorylation abnormalities, and a predisposing electrophysiological substrate . We showed that storm patients have different extent and distribution of endocardial low voltage scar on intracardiac mapping, specific to cardiomyopathy type that may help explain their electrophysiologic vulnerability.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations